A novel, biocompatible and electrocatalytic stearic acid/nanosilver modified glassy carbon electrode for the sensing of paraoxon pesticide in food samples and commercial formulations. (1st September 2020) - Kumaravel, A.; Murugananthan, M.; Mangalam, R.; Jayakumar, S.
Highlights: Low overpotential detection. Obtained lower detection limits. Good recovery rates. Abstract: A simple, biocompatible and an enzyme-free sensing platform was developed for detection of paraoxon. The surface of a glassy carbon electrode was modified with an electrodeposition of stearic acid/nanosilver composite at −0.7 V for 40 s. The paraoxon undergoes electro-reduction at −550 mV on the modified electrode, and the limits of detection (LOD) was calculated as 0.1 nM (S/N = 3) using differential pulse voltammetry which is lower than that of the existing materials reported. The high stability observed with the modified electrode for prolonging period indicated that the sensitivity of the electrode remains active for several runs of the analysis. The developed analytical strategy was implemented for onion and paddy grain samples and good recovery rates were observed. Also, it was applied for analyzing the purity of the commercial paraoxon sample. The reliability of the developed strategy was confirmed by comparing the results of electrochemical approach with that of HPLC technique.